ANALISIS KETERLIBATAN PEREMPUAN DALAM PENYELENGGARAAN PEMILU (Studi Kasus : TPS Khusus Perempuan Pada Pemilu Tahun 2020 di Denpasar) - Putrika, Dwitty Ayuning; Noak, Piers Andreas; Erviantono, Tedi; Duarte, Efatha Filomeno Borromeu (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
This research aims to understand the process of forming TPS 17 officers in South Denpasar, which consists entirely of women, as well as the obstacles they face in carrying out their duties in an area with a patriarchal culture, and how to overcome them. This research is a qualitative study with primary data obtained from interviews with members of female election organizers in Denpasar City, as well as secondary data from published documents and scientific articles. Analysis was carried out using purposive sampling and qualitative descriptive techniques. The research results show that the selection process for female TPS officers involves strict requirements such as integrity, qualifications and commitment. One of the main obstacles is society's lack of confidence in women's ability to carry out this task, which is often influenced by patriarchal values. Female officers, like Ibu Wati and her colleagues, face this challenge by working hard and showing good performance. Support from their family and friends also plays an important role in increasing self-confidence. Through dedication and real results, they succeeded in proving that women are capable of carrying out TPS duties effectively, which is also a form of empowerment and resistance to existing gender stereotypes.